Double Rule In: Concomitant Acute Coronary Occlusion and Pulmonary Embolism - Maharaj, Valmiki (JACC Case Rep, 2019)
Computed tomography angiography is frequently used for double rule out of obstructive coronary artery disease and pulmonary embolism in patients presenting to the emergency department with acute chest pain, but it is rare to see concomitant acute coronary occlusion and pulmonary embolism on the same computed tomography angiography scan. (Level of Difficulty: Beginner.)